2019
DOI: 10.1021/acs.langmuir.8b04122
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Fluorescence Microscopy Study of the Production of K1 Capsules byEscherichia coli: Evidence for the Differential Distribution of the Capsule at the Poles and the Equator of the Cell

Abstract: The production of Escherichia coli K1 serotype capsule was investigated using direct stochastic optical reconstruction microscopy with live bacteria and graphene oxide-coated coverslips, overcoming many morphological artifacts found in other high-resolution imaging techniques. Super-resolution fluorescence images showed that the K1 capsular polysaccharide is not uniformly distributed on the cell surface, as previously thought. These studies demonstrated that on the cell surfaces the K1 capsule at the poles had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 69 publications
4
31
0
Order By: Relevance
“…However, the novel images presented in the study seem to suggest that capsule production stems from discrete foci on the surface of the cell and does not diffuse around the cell surface covering it uniformly. This is further supported by the post hoc analysis of microscopic images of K. pneumoniae from previous studies (Evrard et al, ), and by the results from a more recent study on the production of the Escherichia coli capsule K1, which is secreted through the same biosynthesis pathway (Phanphak et al, ). Using super resolution microscopy and high pressuring light scattering chromatography, the latter study showed that the capsule forms rafts or discrete brushes on the surface of the cell.…”
Section: Commentarysupporting
confidence: 56%
See 1 more Smart Citation
“…However, the novel images presented in the study seem to suggest that capsule production stems from discrete foci on the surface of the cell and does not diffuse around the cell surface covering it uniformly. This is further supported by the post hoc analysis of microscopic images of K. pneumoniae from previous studies (Evrard et al, ), and by the results from a more recent study on the production of the Escherichia coli capsule K1, which is secreted through the same biosynthesis pathway (Phanphak et al, ). Using super resolution microscopy and high pressuring light scattering chromatography, the latter study showed that the capsule forms rafts or discrete brushes on the surface of the cell.…”
Section: Commentarysupporting
confidence: 56%
“…Interestingly, Phanphak and colleagues also show that the capsule displays a bimodal thickness in the rafts at the cell poles, rather than the monomodal thickness that characterizes the capsule on the remaining parts of the cell envelope (Phanphak et al, ). This could explain the increased deformation on the poles observed in Δ wza and Δ wzy mutants.…”
Section: Commentarymentioning
confidence: 99%
“…Finally, infections of target bacteria with lysates from bacteria with the same CLT seem both more reproducible and effective, compared to those lysates produced from bacteria with different CLT ( Figure S7), suggesting that stochasticity in infections can also be a consequence of capsule-phage interactions, e.g. if the former is unevenly distributed throughout the cell envelope (Phanphak et al 2019) or if there is stochasticity in its expression (Krinos et al 2001, Tzeng et al 2016. Future experiments tackling diverse ecological scenarios (e.g., co-cultures between three or more strains) will help understanding the causes and consequences of multiple infections producing poly-lysogens for competitive and evolutionary interactions between strains.…”
mentioning
confidence: 96%
“…Most literature suggests that the rapid turnover of capsular serotypes is due to biotic pressures, such as phage predation, cell-to-cell interactions, the host adaptive immune system, or protozoa grazing (Cobey andLipsitch 2012, Mostowy and, but more work is needed to elucidate whether the abiotic conditions of the environment also play a role in the diversification of the capsule composition. For example, different capsules could be better adapted to certain poor environments because of their different propensity to aggregate or because of their organization at the cell surface (Phanphak et al 2019, Rendueles 2020. It could also be that different serotypes are associated to specific functions or fitness advantages (Ofek et al 1993).…”
Section: R Ementioning
confidence: 99%